El intelecto agente aristotélico como “intelecto personal” según Leonardo Polo - Solomiewicz, Adam (Sapientia, 2019)
The agent intellect is one of Aristotle's most eminent philosophical findings. The Philosopher indicated that in human intellection it is necessary to distinguish between the patient intellect and – separated from it and superior to it – the agent intellect. This conception has been treated throughout the centuries by several philosophers of Aristotelian inspiration, among whom the Arab Aristotelians and St. Thomas Aquinas stand out. Some of the questions of the agent intellect (such as its ontological status) did not find satisfactory solutions. Leonardo Polo (1926-2013) proposed to “personalize” the Aristotelian agent intellect, that is, to equate it with the human actus essendi (the personal nucleus or intimacy of the human person). Such a human personal intellect is equivalent to transcendental human cognitive activity whose two aspects are the following: 1. "to transparent" the cognitive light donated by the Personal God (the Pure Act from the Aristotelian point of view); 2. to "illuminate" the human cognitive capacities suitable to know their corresponding themes, i.e. to illuminate the intelligence (the patient intellect) that with such light knows its intelligible objects.